Objective Evaluation Method for Chlorine Detector Tubes - Rozsypal, Tomas; Kobliha, Zbynek (Defence Science Journal, 2016)
A tristimulus colourimetric method for the evaluation of detection response of chlorine detector tubes has been developed. The method is based on the suction of chlorine through the respective tube, followed by objective evaluation of the colouration change by means of a reflectance spectrophotometer. This eliminates errors in evaluation and allows identification of further positive attributes of detector tubes (e.g. response time, limit of detection). The method is suitable for tubes produced by various manufacturers. Oritest, Dräger and Gastec tubes were selected and measured. The response time of tubes lasted up to 30 s. The limit of detection was lowered up to four times. Reflectance curves of tubes before and after colouration change were recorded. The method also created the possibility of quantitative measurement by non-quantitative detector tubes.